Complete mitochondrial genome of Niphades castanea (Coleoptera: Curculionidae). Issue 3 (2nd July 2020) - Fu, Yue; Yu, Jiaojun; Fang, Xiangliang; Shen, Mi; Fu, Jun; Xiao, Yunli
Abstract: Niphades castanea Chao is an important insect pest on many plants which belong to genus Castanea. The complete mitochondrial genome of N. castanea was sequenced and analyzed. The phylogenetic relationships between N. castanea and other 41 species in the family Curculionidae were reconstructed using maximum likelihood (ML) methods based on the concatenated nucleotide sequences, the phylogenetic analysis showed that N. castanea is closely related to Hylobitelus xiaoi, which is in accordance with the traditional morphological classification.